Portable Innovation of Structures in Building Prototype Home to Residential Settlement at Disaster Location - Zuhri, Syaifuddin; Subiyantoro, Heru; Ghozali, Imam; Saifuddin, Joumil Aidil (Future Science, 2023)
The development of post-disaster residential building prototypes is a build-ing design prototype intended for disaster homes that have been designed in previous research. The next research that’s improved on the aspect of reliability in terms of the use of structures, materials, and construction used in the prototype that's can be applied in the field according to the needs of users who are comfortable and safe. To find the optimal building design from the aspect of building safety so that it does not collapse, it is necessary to take into the aspects of equilibrium of form, geometric stability, and rigidity shape that can stand upright and function when inhabited. The composition of the building elements consists of floor, wall, and roof elements that are composed of building materials using light weight steel. The structural arrangement used uses the truss method as a structural system that is simple and easy to implement. To get confidence that the building can stand upright and not collapse due to the loads acting on it, it is necessary to do an analysis using the problem-solving analysis method in stages on the building structure. The treatment results found that the level of displacement of the building caused by horizontal loads did not significantly affect the shape of the building, meaning that the building could still function according to its use. The use of light steel material for the Canal C-75 Smart Truss Classic Frame which is used as a roof frame and wall structure is still able to overcome vertical or horizontal loads acting on the building. This is done so that the confidence that the planned building prototype can be implemented safely in the field as expected.